Nutrient status of scavengable feed resources in crop and gizzard contents of three genotypes of ducklings (Bangladesh Journal of Animal Science, 2014)
An investigation was carried out with 54 scavenging ducklings of three genotypes belonging to three age groups (6, 10 and 14 weeks) taking from 3 areas reared under two feeding regimes. The birds were sacrificed from farmers house between 4.0 and 5.0 P.M. They were dissected to identify crop and gizzard contents (CGC). Cereal grains, bran, green forages, insects and worms were the main CGC and their composition varied significantly (p